The Effect of Emotional Intelligence and Learning Behavior on Students' Understanding of Accounting In Grade X Accounting Department - Gultom, Jelita Maribet; Hanu, La (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The problem in this study is the low understanding of accounting in class X students majoring in Accounting at SMK Negeri 1 Medan. The purpose of this study is to determine the effect of emotional intelligence on the understanding of accounting in class X students majoring in Accounting at SMK Negeri 1 Medan, and to determine the effect of learning behavior on the understanding of accounting in class X students majoring in Accounting at SMK Negeri 1 Medan. This study was conducted at SMK Negeri 1 Medan. The population in this study were all class X AKL students at SMK Negeri 1 Medan, totaling 142 people. The sampling technique used was simple random sampling with a sample size of 105 respondents. The data collection technique in this study was a questionnaire with a Likert scale. Data were analyzed using Partial Least Square (PLS) analysis techniques with the help of SmartPLS software. The tests carried out included PLS Algorithm, Bootstrapping, and hypothesis testing using p-values with significance less than 0.05. The results of the analysis showed that all outer loading values were above 0.6 and AVE above 0.5 which indicated that construct validity was met. Based on the hypothesis testing, emotional intelligence has a significant effect on students' accounting understanding with a p-value of 0.000 (<0.05), so the hypothesis is accepted. Likewise, learning behavior has a significant effect on students' accounting understanding with a p-value of 0.000 (<0.05), so the hypothesis is also accepted. Therefore, it can be concluded that emotional intelligence and learning behavior have a positive effect on the accounting understanding of class X AKL students at SMK Negeri 1 Medan